2020
DOI: 10.1016/j.patter.2020.100116
|View full text |Cite
|
Sign up to set email alerts
|

AI Naturalists Might Hold the Key to Unlocking Biodiversity Data in Social Media Imagery

Abstract: Summary The increasing availability of digital images, coupled with sophisticated artificial intelligence (AI) techniques for image classification, presents an exciting opportunity for biodiversity researchers to create new datasets of species observations. We investigated whether an AI plant species classifier could extract previously unexploited biodiversity data from social media photos (Flickr). We found over 60,000 geolocated images tagged with the keyword “flower” across an urban and rural loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…These same patterns were mirrored at the class level with the highest number of returns for Flickr being Magnoliopsida , a class of flowering plants, and the second highest was Aves . These results also support findings presented in [ 11 ] where results showed that Flickr is rich in plant-related data mainly dominated by non-native flowering plants. However, that research focused only on plants and does not perform comparison between Flickr and citizen science data portals.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These same patterns were mirrored at the class level with the highest number of returns for Flickr being Magnoliopsida , a class of flowering plants, and the second highest was Aves . These results also support findings presented in [ 11 ] where results showed that Flickr is rich in plant-related data mainly dominated by non-native flowering plants. However, that research focused only on plants and does not perform comparison between Flickr and citizen science data portals.…”
Section: Resultssupporting
confidence: 92%
“…The use of iEcology approaches is increasing as it provides low-cost and fast data collection, pattern identification, and visualisation of nature-related data. In particular, the study of [ 11 ] investigates whether a plant species image classifier can be used to extract relevant plant observations from Flickr, using a general search term of ‘flower’. Analyses showed that automated methods have the potential to help identify wildlife-related imagery data on social media, especially when photos were focused on single native species in rural situations or when classification was performed at genus or class level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the use, and diversity of uses, of social media analysis across the environmental sciences has rapidly increased (Ghermandi & Sinclair, 2019). Social media has been used to develop species distribution models (August, Pescott, Joly, & Bonnet, 2020), measure aesthetic and recreational ecosystem services (Van Zanten et al, 2016;Graham & Eigenbrod, 2019), track illegal wildlife trade (Di Minin, Fink, Tenkanen, & Hiippala, 2018), and determine the role of wildlife in nature-based tourism (Hausmann et al, 2017). The abundance and availability of data on these platforms -many now 15 years old, open the door for more research.…”
Section: Introductionmentioning
confidence: 99%